Best Practices in Cybersecurity Training: Enhancing Employee Awareness to Mitigate Risks - Sreeharsha Amarnath Rongala (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This technical article explores the critical role of cybersecurity training programs in addressing the growing challenges of cyber threats in modern organizations. The article examines how human factors contribute to security vulnerabilities while also presenting opportunities for strengthening organizational defense through comprehensive training initiatives. Through this detailed article of current research and industry reports, this article investigates the implementation of structured training approaches, measurement frameworks, and cultural transformation strategies. The article encompasses key aspects including baseline assessments, multi-tiered training architectures, performance metrics, security-conscious culture development, technical integration through learning management systems, compliance documentation, and future-proofing methodologies. The article demonstrates that organizations implementing comprehensive security awareness programs experience significant improvements in threat detection, incident response, and overall security posture while highlighting the importance of leadership engagement and continuous adaptation in maintaining effective cybersecurity training programs.